South African stakeholder views of the competency requirements of facilities management graduates - Azasu, Samuel; Adewunmi, Yewande; Babatunde, Oluwayomi (International Journal of Strategic Property Management, 2018)
The aim of this study is to evaluate South African stakeholder views of the content of the recently developed postgraduate course in Facilities Management at the University of the Witwatersrand in South Africa. The study was done using a questionnaire survey of a cross-section of professionals registered with the South African Facilities Management Association (SAFMA). It covers technical, personal, interpersonal and professional skills as well as the ability to conceive, design, implement and operate business systems. It also highlights the degree of importance of these skills. The findings of this research will enable those designing FM programmes of study to ensure that their curricula are current and relevant to the needs of the relevant stakeholders within their contexts. The paper goes beyond previous research in the built environment in specifying the requisite proficiency levels in terms of the relevant skills and competencies.